Timing of Calorie Restriction in Mice Impacts Host Metabolic Phenotype with Correlative Changes in Gut Microbiota - Liying Zhang (American Society for Microbiology, 2019)
ABSTRACT Calorie restriction (CR) is accompanied by self-imposed daily restriction of food intake and an extended fasting period between meals. The impact of restricting feeding to the dark or light phase on the effects of CR remains elusive. Here, light-fed CR mice showed physiological changes, such as muscle loss, concomitant with changes in the gut microbiota structure and composition. After switching to ad libitum access to food, light-fed mice had a period of food-craving behavior and short-lived physiological changes, while dark-fed mice displayed lasting changes in fat accumulation, glucose metabolism, intestinal barrier function, and systemic inflammatory markers. Moreover, the gut microbiota was modulated by when the food was consumed, and the most abundant Lactobacillus operational taxonomic unit (OTU) promoted by CR was enhanced in dark-fed mice. After switching to ad libitum feeding, the gut microbiota of dark-fed mice returned to the state resembling that of mice fed normal chow ad libitum, but that of light-fed mice was still significantly different from the other two groups. Together, these data indicate that for CR, restricting food consumption to the active phase brought better metabolic phenotype associated with potentially beneficial structural shifts in the gut microbiota. IMPORTANCE Aberrant feeding patterns whereby people eat more frequently throughout the day and with a bias toward late-night eating are prevalent in society today. However, whether restriction of food to daytime in comparison to nighttime, coupled with restricted calorie intake, can influence gut microbiota, metabolism, and overall health requires further investigation. We surveyed the effects of the shift in feeding time on gut microbiota and metabolic phenotype in calorie-restricted mice and found that avoiding eating during the rest period may generate more beneficial effects in mice. This work strengthens the evidence for using “when to eat” as an intervention to improve health during calorie restriction.